Comprehensive dental and surgical management of patients with congenital insensitivity to pain with anhidrosis: a systematic review of reported cases and management strategies - Fatani, Bader A.; Bin-Salah, Mohammed A.; Mahdi, Abdulaziz A.; Almuhaythif, Muhannad A. (International Journal Of Community Medicine And Public Health, 2024)
Congenital insensitivity to pain is a rare condition that is usually detected in late toddlerhood, a time when children are very active and prone to getting hurt without feeling pain. Despite being protected from external dangers, individuals with this condition tend to harm themselves by biting their tongue, lips, and fingers, leading to significant damage. Children who cannot sense pain and have mental challenges are more vulnerable to infections and slow-healing ulcers. The atypical pain is caused by the absence of specific nerves and nerve responses to harmful stimuli. While previous reports have impressed on oral and dental issues related to congenital insensitivity to pain with or without anhidrosis and how they are managed surgically and dentally, there hasn't been a systematic review gathering all oral and dental findings of this condition. Therefore, our current systematic review aims to examine the complete dental and surgical treatment of patients with congenital insensitivity to pain with anhidrosis (CIPA) by discussing documented cases and treatment methods.